2011
DOI: 10.5352/jls.2011.21.6.796
|View full text |Cite
|
Sign up to set email alerts
|

Extracts of Allium fistulosum Attenuates Pro-Inflammatory Action in the Lipopolysaccharide-Stimulated BV2 Microglia Cells

Abstract: Microglia are central nervous system (CNS)-resident professional macrophages that function as the principal immune cells responding to pathological stimulations in the CNS. Activation of microglia, induced by various pathogens, protects neurons and maintains homeostasis in the CNS, but severe activation causes inflammatory responses secreting various neurotoxic molecules such as nitric oxide (NO), prostaglandin E2 (PGE2) and pro-inflammatory cytokines. Allium fistulosum, a member of the onion family, is mainly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…In an MTT assay, all extracts except the ethanol extract of the root, effectively suppressed both the production of mRNA and the protein expression of iNOS and COX-2 enzymes at the concentrations of 50 µg/mL. The cellular concentrations of various pro-inflammatory cytokines, including TNF-α, IL-1ß and IL-6 were also significantly down regulated at the mRNA level (Park S-H et al 2011a).…”
Section: Allium Fistulosum Lmentioning
confidence: 98%
“…In an MTT assay, all extracts except the ethanol extract of the root, effectively suppressed both the production of mRNA and the protein expression of iNOS and COX-2 enzymes at the concentrations of 50 µg/mL. The cellular concentrations of various pro-inflammatory cytokines, including TNF-α, IL-1ß and IL-6 were also significantly down regulated at the mRNA level (Park S-H et al 2011a).…”
Section: Allium Fistulosum Lmentioning
confidence: 98%
“…iNOS↓, COX-2↓, TNF-α↓, IL-6↓, IL-1β↓ [38] Aqueous extracts of Welsh onion green leaves LPS-activated RAW 264.…”
Section: Lps-stimulated Bv2mentioning
confidence: 99%
“…Many studies have confirmed that, in the process of inflammation, the expression levels of NO, TNF-α, COX-2 and iNOS are increased. Another study explored the anti-inflammatory effect of leek extracts on LPS-stimulated BV2 microglia [38]. Four different extraction methods used to extract leeks were studied, and it was found that all four extracts could effectively inhibit the mRNA and protein expression levels of iNOS and COX-2 at the cellular level.…”
Section: Anti-inflammatory Activitiesmentioning
confidence: 99%
“…염증반응은 우리 몸을 보호하기 위 1 한 면역체계 반응이지만 지속적인 염증반응의 진행은 세포 조직의 손상을 초래하여 암, 뇌질환, 알츠하이머병, 관절염, 천식, 염증성 장질환 및 동맥경화 등 여러 질병뿐만 아니라 노화의 직·간접적 원인이 되는 것으로 알려져 있다 [2][3][4]. 대 식세포는 염증반응에 관여하는 주요 세포로 손상 부위로의 면역세포의 이동과 Tumor necrosis factor (TNF)-α, Interleukin (IL)-1β 및 IL-6 등의 pro-inflammatory cytokine 분비에 관여 하는 등 매우 중요한 역할을 한다 [1,3,[5][6][7].…”
Section: Introductionunclassified